Searches for the violation of Pauli exclusion principle at LNGS in VIP(-2) experiment. Issue 4 (May 2016) - Shi, H; Bartalucci, S; Bertolucci, S; Berucci, C; Bragadireanu, A M; Cargnelli, M; Clozza, A; Curceanu, C; De Paolis, L; Di Matteo, S; d'Ufflzi, A; Egger, J-P; et al.
Abstract: The VIP (Violation of Pauli exclusion principle) experiment and its follow-up experiment VIP-2 at the Laboratori Nazionali del Gran Sasso (LNGS) search for X-rays from Cu atomic states that are prohibited by the Pauli Exclusion Principle (PEP). The candidate events, if they exist, will originate from the transition of a 2p orbit electron to the ground state which is already occupied by two electrons. The present limit on the probability for PEP violation for electron is 4.7 ×10 –29 set by the VIP experiment. With upgraded detectors for high precision X-ray spectroscopy, the VIP-2 experiment will improve the sensitivity by 2 orders of magnitude.